COVID-19: General and Oral Manifestations in Children, Impact on Pediatric Dentistry and Future Perspective - Sah, Barun Kumar; Sundas, Sunanda; Dhakal, Neha (Journal of Nepalese Association of Pediatric Dentistry, 2020)
(COVID-19) has spread rapidly across the globe, becoming a major public health concern for countries around the world. Despite worldwide efforts to contain viral spread, the outbreak has not shown any promising signs of containment yet. The coronavirus disease 2019 is a respiratory infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). It is mainly transmitted through respiratory droplets and close contact. As COVID-19 cases have been reported among children as well, there is an increased risk of acquiring the disease through these Silent Carriers who present as asymptomatic with mild or moderate clinical viral infection. The American Academy of Pediatric Dentistry (AAPD) is constantly revising their checklist for re-emergence in pediatric dental practice during the COVID-19 pandemic. Pediatric dentists should keep a high level of awareness to help patients, minimize risk and prevent viral spread. During this period of pandemic, management of child’s oral health presents specific difficulties related to the infectious spread of the disease. The aim of this article is to review the Covid-19 infection in children, its impact on pediatric oral health, challenges for pediatric dentistry and future perspective.